Combination of paromomycin plus human anti-TNF-α antibodies to control the local inflammatory response in BALB/ mice with cutaneous leishmaniasis lesions. Issue 1 (October 2018) - Schwartz, Juana; Moreno, Esther; Calvo, Alba; Blanco, Laura; Fernández-Rubio, Celia; Sanmartín, Carmen; Nguewa, Paul; Irache, Juan M.; Larrea, Esther; Espuelas, Socorro
Highlights: Cutaneous leishmaniasis topical therapy with paromomycin and anti-TNFα antibodies. The combination produced similar reduction of parasite load. The combination was more effective to control the local inflammation. PM showed both antileishmanial/anti-inflammatory effect further enhanced with anti-TNFα antibodies. Abstract: Background: Cutaneous leishmaniasis (CL) skin lesions are the result of a deregulated immune response, which is unable to eliminate Leishmania parasites. The control of both, parasites and host immune response, is critical to prevent tissue destruction. The skin ulceration has been correlated with high TNF-α level. Objective: Because human anti-TNF-α antibodies (Ab) have been successfully assayed in several mice inflammatory diseases, we hypothesized that their anti-inflammatory effect could optimize the healing of CL lesions achieved after topical application of paromomycin (PM), the current chemotherapy against CL. Methods and results: We first compared the in vitro efficacy of PM and Ab alone and the drug given in combination with Ab to assess if the Ab could interfere with PM leishmanicidal activity in L . major- infected bone marrow-derived macrophages. The combination therapy had similar antileishmanial activity to the drug alone and showed no influence on NO production, which allows macrophage-mediated parasite killing. Next, we demonstrated in an in vivo model of Imiquimod®-induced inflammation that topical Ab and PM inhibit the infiltration of inflammatory cells in the skin. In the efficacy studies in L . major- infected BALB/c mice, PM combined with Ab led to a sharp infection reduction and showed a stronger anti-inflammatory activity than PM alone. This was confirmed by the down-regulation of TNF-α, IL-1β, iNOS, IL-17, and CCL3 as well as by a decrease of the neutrophilic infiltrate during infection upon treatment with the Ab. Conclusions: In terms of parasite elimination and inflammation reduction, topical application of Ab in combination with PM was more effective than the drug alone.